Effects of guanidine acetic acid supplementation from gestation to lactation on reproductive performance, colostrum quality, blood biochemistry, and intestinal microflora diversity of sows - Cong, Guanglei; Xia, Shuangshuang; Liu, Chunxue; Li, Junbo; Hung, Ifen (Frontiers in Veterinary Science, 2024)
This experiment aimed to study the effects of guanidine acetic acid (GAA) on reproductive performance, lactation performance and blood biochemical indices of sows, as well as the performance of offspring piglets. A total of 20 sows (Landrace × Yorkshire, parity 4) were used. Half of the sows in each parity were fed a control diet (CG; basic diet, n = 10) or GAA diet (basic diet +1 g/kg GAA, n = 10) from the 85th day of gestation until weaning. The study results are presented as follows: Supplementation of GAA from late gestation to lactation did not adversely affect sow feed intake, backfat thickness, or blood routine indexes (p > 0.05). GAA supplementation showed a tendency to increase the number of healthy piglets and their birth activity (p = 0.06; p = 0.08), while significantly increasing the IUGR score of piglets (p < 0.05). GAA supplementation significantly increased colostrum protein content (p < 0.05) and tended to increase daily milk yield in sows (p = 0.07). GAA supplementation increased the level of immunoglobulin A in sow colostrum (p < 0.05) and showed a tendency to increase proline content (p = 0.10). GAA supplementation significantly decreased triglyceride content in sow cord blood (p < 0.05), with no significant effects observed on HDL-C, LDL-C, TC, and GLU (p > 0.05). GAA supplementation significantly increased eNOS levels in sow cord blood (p < 0.05), while showing no significant effects on IL-6 and IL-10 (p > 0.05). GAA supplementation did not significantly affect the α diversity of sow intestinal flora (ACE, Shannon, Chao1, Simpson, observed_otus, pielou_e, and good_cover), but PCoA analysis revealed differences in intestinal flora structure between groups. Additionally, GAA decreased the relative abundance of Sarciha and unidentified_ruminococcaceae and increased the relative abundance of Lactobacillus, Parabacteroides, and Pedobacter in the gut. GAA boosts nitric oxide synthase in sows’ umbilical cord blood, enhancing placental blood vessel development. This improves piglet health and vitality, increases beneficial gut bacteria (Lactobacillus, Parabacteroides, Pedobacter), and raises colostrum protein levels and lactation volume, leading to better piglet growth and performance.